VILLAGE OFFICIALS’ PERFORMANCE IN PUBLIC SERVICES IN MANGKUHUNG VILLAGE, MIRI MANASA DISTRICT, GUNUNG MAS REGENCY - Andreas, Andreas; Rahmadanita, Annisa (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2024)
The Mangkuhung Village officials’ performance in providing public services to has not been optimal as evidenced by frequent complaints regarding the services provided. This quasi-qualitative research aims to obtain a general description and analyze the performance of village officials in providing public services in Mangkuhung Village. The research results showed that some officials have understood their duties and functions, but the village government had not disseminated the standard operating procedure for public services to the people, and there had been no routine training conducted by village officials. In the innovation aspect, public services were still carried out conventionally. As for the speed and accuracy of work, it was quite well, although there were some employees were not quick enough in responding to public complaints. In the aspect of cooperation, there were obstacles related to the lack of routine coordination both internally and externally. In conclusion, the performance of Mangkuhung Village officials in giving public services was in fairly good category. This research recommends strengthening budget priorities for training/technical guidance activities to increase the capacity of village officials, and to strengthen telecommunications networks in Mangkuhung Village. Keywords: Officials’ Performance, Public Service, Service Innovation.